(Invited) Silicon-Based Nanocomposites for Thermoelectric High Temperature Waste Heat Recovery. (14th September 2015) - Schierning, Gabi; Wiggers, Hartmut; Schmechel, Roland
Abstract : Thermoelectric generators can recover waste heat from high temperature heat sources. Given a scalable and affordable technology, this may be part of a future energy mix. For this, suitable thermoelectric converter materials need to be indentified and their efficiency improved. Besides, thermoelectric generators may also be further developed for high temperature applications. We here present results on silicon-based nanocomposites and thermoelectric generators which can meet these criteria.